Perizinan Pembangunan Tersus (Terminal Khusus) (Studi Kasus CV Bina Lestari Jaya) Di Pangkalpinang Bangka Belitung - Supartini Supartini; Vivid Dekanawati; Rizki Dwi Wardoyo (Sekolah Tinggi Maritim Yogyakarta, 2020)
The activities of the shipping sector are divided into two, commercial and non-commercial shipping. In order to support sea transportation facilities, infrastructure in the form of a port is needed. The port is a stop / terminal of the ship after a cruise. At the port the ship carries out a variety of activities, such as the ups and downs of passengers, loading and unloading of goods, refueling, and fresh water. In order to support business activities for its own interests, a Special Terminal (Tersus) can be built. For the construction of the tersus, CV Bina Lestari Jaya coordinates with the government and prepares concepts thoroughly, takes care of licensing which has quite complicated stages and requirements, because it requires a survey with accurate data, both location determination, feasibility studies both on land and at sea / water. It also needs to consider the economic aspects, efficiency, environmental impact and K3 (Occupational Health and Safety). Furthermore, a feasibility study was accompanied by a Palembang Class 1 Navigation District technical team. In this study, the authors used a qualitative research method with a descriptive approach.